Osteosarcoma in a Patient With Pseudohypoparathyroidism Type 1b Due to Paternal Uniparental Disomy of Chromosome 20q. (17th February 2017) - Park, Hye‐Sun; Kim, Chang Gon; Hong, Namki; Lee, Seok Joo; Seo, Da Hea; Rhee, Yumie
ABSTRACT: It is assumed that a persistent high level of parathyroid hormone (PTH) might have a relation with bone malignancy. However, there has been no report of osteosarcoma associated with pseudohypoparathyroidism type 1b (PHP1b), which is accompanied by high PTH. PHP1b is the result of resistance to PTH in certain end‐organ tissues, especially the kidney; the response in bone is unaffected because it normally expresses stimulatory G protein equally from both parental alleles. A 21‐year‐old male, presenting with gum swelling at the right mandible, was referred to a dental clinic. A curative surgical resection by segmental mandibulectomy was performed and the pathologic findings of the mass were consistent with osteoblastic osteosarcoma. His laboratory results showed a low calcium level despite high PTH, and he did not have any features of Albright hereditary osteodystrophy; therefore, PHP1b was suspected. Multiplex ligation‐dependent probe amplification and microsatellite marker analyses of chromosome 20 confirmed the diagnosis and identified paternal uniparental disomy of chromosome 20q (patUPD20). To the best of our knowledge, this is the first report of osteosarcoma in a patient with PHP1b due to patUPD20. © 2017 American Society for Bone and Mineral Research. Abstract : Chronically high level of parathyroid hormone (PTH) might be associated with the development of bone tumor. A patient in this report had a pseudohypoparathyroidism type 1b (PHP1b) by paternal uniparental disomy of chromosome 20q who developed a mandibular osteosarcoma. PHP1b is characterized by specific resistances in the proximal renal tubule but sensitive responses in the bone to the persistent PTH elevation. It is possible that persistently elevated PTH could have been pernicious to the bone tumor cells.